Baricitinib for the treatment of rheumatoid arthritis. (1st September 2016) - Kubo, Satoshi; Nakayamada, Shingo; Tanaka, Yoshiya
ABSTRACT: Introduction : Rheumatoid arthritis (RA) is characterized by systemic synovitis causing joint destruction. With the development of biological disease-modifying anti-rheumatic drugs (bDMARDs) and combination of conventional DMARDs, clinical remission is perceived as an appropriate and realistic goal in many patients. However, bDMARDs require intravenous or subcutaneous injection and some patients fail to respond to bDMARDs or lose their primary response. Under the circumstances, targeted synthetic DMARDs (tsDMARDs), which are orally available low-molecular weight products, have been emerging. Five phase 3 trials of Baricitinib, a JAK1 and JAK2 inhibitor, have been performed and showed high clinical efficacy in patients with active RA and naïve to sDMARDs or an inadequate response to sDMARDs, MTX or bDMARDs. There was a favorable response for clinical and functional parameters in studies with placebo, MTX and adalimumab as comparator. It is also reported that safety was tolerable within the limited study period. Areas covered : We here review the recent progress in the development of baricitinib and its potential for the treatment of RA. Expert commentary : Although baricitinib is only one of the highly effective DMARDs that has a new mode of action, it will bring new concepts for rheumatology in the future.